What factors play a role in preventing self-immolation?Results from a case-control study in Iran - Hosein Karim (Journal of Injury and Violence Research, 2015)
Abstract: Background: To investigate factors related to prevention of self-immolation in west of Iran. Methods: In a case-control study, 30 consecutive cases of deliberate self-inflicted burns admitted to the regional burn center (Imam Khomeini hospital in Kermanshah province, Iran) were compared with controls selected from the community and matched by sex, age,district-county of residence, and rural vs urban living environment. The following characteristics relevant to preventing self immolation were collected from all cases and controls: main domestic fuel used in the household, awareness about complications of burn injuries, and use of counseling services. Results: Descriptive analyses revealed that kerosene was the main domestic fuel in the household for 83% of cases. Not surprisingly, the main means of self-immolation in 93% of the patients was kerosene, with other fuels such as petrol and domestic gas used in remaining cases. The majority of cases and controls were aware of the potential complications of burn injuries. Use of counseling services was more common in controls. Conclusions: All three aspects of preventing self-immolation – having kerosene and other fuels in the home, being aware of the complications of burn injuries, and using counseling services were present in both the cases and controls. This suggests a large portion of residents in rural Iran are potential self-immolation victims. Increasing preventive strategies may reduce risk of suicide by self-immolation.